Simultaneous perturbation stochastic aproximation for Lipshitz functions - Bartkutė, Vaida; Sakalauskas, Leonidas (Lietuvos matematikos rinkinys, 2004)
The convergence conditions of Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm with Gaussian smoothing operator are established in the class of Lipshitz functions.
Keywords: stochastic approximation; Lipshitz function; differential